solve by lagrange's method z(p-q) =z^2+(x+y)^2
Standard pde is Pp+Qq=R,
where p="\\frac{ \\partial z}{\\partial x}" and q="\\frac{ \\partial z}{\\partial y}" .
Comparing the given pde with the standard pde.
We get, P=z, Q=-z, R=z2+(x+y)2
By lagrange method,
"\\frac{dx}{P}=\\frac{dy}{Q}=\\frac{dz}{R}\\\\\n\\frac{dx}{z}=\\frac{dy}{-z}=\\frac{dz}{z^2+(x+y)^2}\\\\"
By taking first equation,
"\\frac{dx}{z}=\\frac{dy}{-z}\\\\\ndx=-dy\\\\\nx=-y+c_1\\\\\nx+y=c_1"
By taking second equation,
"\\frac{dy}{z}=\\frac{dz}{z^2+(x+y)^2}\\\\\ndy=\\frac{z}{z^2+c_1^2}dz \n[ \\space \\text{from first equation}]\\\\\ndy=\\frac{1}{2}\\frac{2z}{z^2+c_1^2}dz"
Integrating both side, we get
"y=\\frac{1}{2}ln(z^2+c_1^2)+c_2\\\\\ny-ln\\sqrt{(z^2+(x+y)^2)}=c_2"
Therefore, the solution is given by
"F(x+y, y-ln\\sqrt{(z^2+(x+y)^2)})=0"
Comments
Leave a comment